2018
DOI: 10.1186/s12955-018-0853-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in small-scaled homelike nursing homes: an 8-month controlled trial

Abstract: BackgroundQuality of life is a clinical highly relevant outcome for residents with dementia. The question arises whether small scaled homelike facilities are associated with better quality of life than regular larger scale nursing homes do.MethodsA sample of 145 residents living in a large scale care facility were followed over 8 months. Half of the sample (N = 77) subsequently moved to a small scaled facility. Quality of life aspects were measured with the QUALIDEM and GIP before and after relocation.ResultsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 56 publications
0
34
1
1
Order By: Relevance
“…Kok points to small care institutions as more friendly than large ones. They relieve their residents' fears and thereby improve quality of their life [19]. Those results do not match these of this author, where size of institutions had no effect on satisfaction with life.…”
Section: Satysfakcja Z żYcia Starszych Mieszkańców Domów Pomocy Społecontrasting
confidence: 64%
See 1 more Smart Citation
“…Kok points to small care institutions as more friendly than large ones. They relieve their residents' fears and thereby improve quality of their life [19]. Those results do not match these of this author, where size of institutions had no effect on satisfaction with life.…”
Section: Satysfakcja Z żYcia Starszych Mieszkańców Domów Pomocy Społecontrasting
confidence: 64%
“…Kok badając mieszkańców małych i dużych placówek opieki wskazuje te pierwsze, jako bardziej przyjazne. Wiążą się one ze zmniejszeniem lęku u rezydentów, a co za tym idzie ze zwiększeniem ich jakości życia [19]. Wyniki te nie korespondują z badaniami własnymi, gdzie rozmiar placówki nie miał wpływu na poziom satysfakcji z życia.…”
Section: Satisfaction With the Lives Of Elderly Nursing Homes Residentsunclassified
“…Current research proposes the implementation of quality of life measurements to cover residents' viewpoints on care (Becker et al 2005;Brandenburg & Günther 2015;de Boer et al 2017;Grabowski et al 2014;Hassler & Wolf-Ostermann 2010;Kok et al 2018;Palm et al 2018;Vaarama et al 2008). So far only a few studies investigating subjective quality of life in older people can be found.…”
Section: Introductionmentioning
confidence: 99%
“…So far only a few studies investigating subjective quality of life in older people can be found. They mainly focus on older, multi-morbid patients without dementia (Hassler & Wolf-Ostermann 2010;Holzhausen 2009;Warnke et al 2004), address patients with dementia partly in special settings (Auer, et al 2017;Ettema et al 2005;Gertz & Berwig 2008;Kok et al 2018;Logsdon et al 2002;Palm et al 2018;Sixsmith et al 2008), and consider care-related measures in nursing home residents (Becker et al 2005;Schaal et al 2015;Vaarama et al 2008). According to our research there is still a complete lack of studies on groupliving nursing homes residents in Germany and elsewhere, apart from one preliminary pilot study published in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our best knowledge, no study has investigated the impact of homecare on the health-related QoL based on the QoL measurement metrics pointed out in [8] such as temperature, noise, lightning, familiarity, adequate space, and opportunities to participate in domestic activities; it could be subsequently deduced that if the patient's residence place also provides the same environmental criteria as temperature, familiarity, sufficient food, and water, etc., the patient treated at home will undergo the same healthrelated QoL. In [9], the authors investigated the impact small-scaled nursing care homes have on health outcome-related QoL. They found out that moving from large-scaled to a small-scaled nursing house can improve the aspect of the QoL by reducing the anxiety.…”
Section: Introductionmentioning
confidence: 99%